The displacement impacts of wind power electricity generation: Costly lessons from Ontario - Pejman Bahramian; Glenn P. Jenkins; Frank Milne (Queen's University, Department of Economics, 2020)
The displacement impacts of wind power generation on other generation technologies are estimated for Ontario. In addition, their annual financial benefits, costs, and international stakeholder impacts are measured. For every 100 MWh generated, almost 53 MWh of gas output and 23 MWh of hydro output is displaced, and 19 MWh of power is exported. Ontario loses 826.42 million USD annually from having wind power generation in the system, while the US gains 7.50 million USD through electricity exported from Ontario. Wind power generation has produced an estimated 108.98 million USD in reducing CO2 emissions in the US and Ontario through displacing thermal generation. Comparing the environmental benefits with the net cost to consumers shows the promotion of wind power generation to be largely a waste of Ontario's resources.
Keywords: D61; F18; F64; H23; H25; H43; 330; wind power; thermal displacement; CO2 emissions; stakeholder analysis